A comparative study of porous support from Sayong and Kankara clay - Mohamed Bazin, Maisarah (2015)
A porous supports were fabricated from Sayong ball clay and Kankara clay for wastewater treatment application using simple compaction method. The influence of sintering temperature (900-1200 °C) and starch addition (5-30 wt%) on the physical properties and flexural strength of the porous support were studied. Thermo-gravimetric analysis, particle size distribution, microstructure, phase, porosimetry analysis and strength analysis were studied to characterize the porous supports. The apparent porosity and pore diameter of Kankara porous support (48-55%; 6.62nm) was found to be higher than that of Sayong porous support (0.07-40%; 5.11nm). In contrast, the bulk density of Sayong porous support (1.15-1.93g/cm3) was higher than that of Kankara porous support (1.08-1.25g/cm3). However, the flexural strength of Kankara porous support (34-3MPa) shows sharp decrease compared with Sayong porous support (21-9MPa). This shows that Sayong porous support has better physical properties and flexural strength compared with Kankara porous support. Starch has been a good pore former in fabrication of the ceramic membrane. Sintering temperature and starch content have strong influence on the physical and flexural strength of the porous support. Therefore, the properties of the porous support can be varied by controlling the sintering temperature and starch content.